Modeling mixing and melting in laminar seawater intrusions under grounded ice - M. S. Mamer; A. A. Robel; C. C. K. Lai; E. Wilson; P. Washam (The Cryosphere)
Small-scale ice–ocean interactions near and within grounding zones play an important role in determining the current and future contribution of marine ice sheets to sea level rise. However, the processes mediating these interactions are simplified in large-scale models due to limited observations and computational resources, contributing to uncertainty in future projections. Previous modeling studies have demonstrated that seawater can interact with subglacial discharge upstream of the grounding zone, and recent observations appear to support this possibility. In this study, we investigate turbulent mixing of quasi-laminar intruded seawater and glacial meltwater under grounded ice using a computational fluid dynamics solver. In agreement with previous work, we demonstrate the strongest control on intrusion distance is the speed of subglacial discharge and the geometry of the subglacial environment. We show that, in the fluid regimes simulated here, and expected at ice shelf grounding zones, turbulent mixing plays a negligible role in setting intrusion distance. Basal melting from seawater intrusion produces buoyant meltwater, which may create a negative feedback by chilling and freshening near-ice water, therefore reducing further melting; however, this remains unquantified. The magnitude of modeled basal melt rates from seawater intrusion can be replicated by existing sub-ice-shelf melt parameterizations by modifying the traditionally used transfer coefficients. We conclude that, in times or places when subglacial discharge is slow, seawater intrusion can be an important mechanism of ocean-forced basal melting of marine ice sheets when considering added geometric complexities and ocean conditions.